2019
DOI: 10.17113/ftb.57.04.19.6380
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gum Arabic Enriched with GABA Coating on Oxidative Damage of Walnut Kernels

Abstract: Because of the higher content of unsaturated fatty acids (UNSFA) and phenolics, walnut kernels are vulnerable to oxidative rancidity and browning due to unfavorable postharvest handling procedures. This study investigates the impact of gum arabic coating enriched with γ-aminobutyric acid (GABA) on oxidative rancidity and browning of kernels during storage at 20 °C. The results showed that the walnut kernels coated with gum arabic (5 %) enriched with GABA (0.1 mM) exhibited lower oxidative rancidity and brownin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
2
2
1
Order By: Relevance
“…This study found that compared with the control, 0.05% L-Cys and 0.05% GABA treatments could significantly increase the phenols and antioxidants of loquat fruit. This was similar to the conclusion of Ebrahimzadeh et al [ 35 ] that 1% gum arabic (rich in 5.0 mM GABA) significantly increased the total phenolic content of walnut kernels and delayed the decrease in antioxidant capacity. Postharvest studies of bananas also found that GABA treatment promoted the increase in total phenol content in banana fruits during storage [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…This study found that compared with the control, 0.05% L-Cys and 0.05% GABA treatments could significantly increase the phenols and antioxidants of loquat fruit. This was similar to the conclusion of Ebrahimzadeh et al [ 35 ] that 1% gum arabic (rich in 5.0 mM GABA) significantly increased the total phenolic content of walnut kernels and delayed the decrease in antioxidant capacity. Postharvest studies of bananas also found that GABA treatment promoted the increase in total phenol content in banana fruits during storage [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…These results indicate that the mastic gum coating, as a barrier, reduces the transfer of moisture to the almond kernel tissue and increases its inhibitory effect by increasing the thickness of the coating. Similar results were achieved on the effect of coating almonds or other nuts kernels with different kinds of edible coating materials, and with increasing the thickness of the coating, its inhibitory effect increases [68][69][70][78][79][80][81].…”
Section: Discussionsupporting
confidence: 76%
“…The quantity of lipid oxidation products in the RTF were both similar and dissimilar to previous studies. The peroxide value of walnuts on the purchase day was higher by 43% and 330% compared to those reported by Aghdam and Chee [23,24], respectively. These higher levels could be attributed to the fact we used store-bought walnuts with an unknown harvest date while in both previous studies, walnuts were freshly harvested.…”
Section: Discussioncontrasting
confidence: 60%